The Concept of Event in the Philosophy of Vladimir Bibikhin - Magun, Artemy (Stasis, 2015)
The article deals with the concept of event in Vladimir Bibikhin’s philosophy. It is shown that Bibikhin, like many contemporary philosophers, considers this concept to be central to today’s thought. Following Heidegger in part, he offers an analysis of event, mainly based on the material of Russian history. Bibikhin builds up a structure of the concept of event (which I reconstruct here). It seems to consist of the following aspects: lightninglike instantaneity, the effect of “rapt” or “capture” made on its participants, spectacularity, constitution of right, finally, the pendulumlike oscillation between mobilization and demobilization. In general, Bibikhin gives a more complex and elaborate notion of event than Heidegger even does, and unlike Heidegger, and even more unlike Badiou, Bibikhin is highly attentive to the spectacular and aesthetic component of event. He considers this spectacular component to be constitutive even though it in no way undermines the ontological status of event.